(untitled) (Research, Society and Development, 2021)
The aim of the present study consisted on the evaluation of knowledge and attitudes of students belonging to the Dental School of the Federal University of Uberlandia (UFU), about HIV/AIDS. This cross-sectional study used a questionnaire to collect individual information with undergraduate students, of the 7th and 8th semester. The results were analyzed by Microsoft Excel and were qualitatively and quantitatively evaluated. The sample consisted of 61 students. Regarding the perception of HIV and the experiences during the dental practice, 59% of the participants stated that they had provided care to at least one self-declared HIV positive patient. In this scenario, 26% of the surveyed participants reported having suffered some type of biological accident. About 31% of respondents stated that a seropositive dental surgeon should not continue practicing his profession without informing his patients of his serological status. Regarding the use of goggles, 19% of the participants did not mention it as personal protective equipment when attending. Therefore, the knowledge evaluation and the student´s attitudes are adequate regarding virus development, transmission and oral manifestations. However, it was observed the lack of understanding, by part of the sample, regarding biosafety measures, handling after a biological accident, and civil and criminal responsibility.